Scratch-Assisted Issue, Discussion, Establish, and Apply (IDEA) Learning Model to Improve Students’ Problem-Solving Skills Evaluated from Their Curiosity - Sumarno, Wahyu Septiadhi; Winarti, Endang Retno (Journal of the Indonesian Mathematics Education Society, 2025)
The purpose of this study was to test the effectiveness of scratch-assisted Issue, Discussion, Establish, and Apply (IDEA) learning in improving problem-solving skills and to describe problem-solving skills in terms of curiosity. The research method used was a mixed method with a sequential explanatory design. Subjects were taken as many as 6 research subjects based on the level of curiosity using purposive sampling techniques in class VII students of SMP Negeri 1 Toroh in the 2024/2025 academic year. Quantitative data analysis includes normality and homogeneity tests, actual completeness limit completeness tests, classical completeness tests, proportion difference tests, significant increase tests. Qualitative data analysis includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that (1) mathematics learning using the scratch-assisted Issue, Discussion, Establish, and Apply (IDEA) model is effective in improving problem-solving skills, (2) there is an influence between curiosity and students' mathematical problem-solving skills of 63.2%, (3) subjects with a high curiosity category are able to meet all indicators of problem-solving skills; Subjects with a moderate curiosity category were only able to meet three indicators of problem-solving ability; subjects with a low curiosity category were only able to meet two indicators of problem-solving ability.